Persepsi Auditor Eksternal Dan Klien Terhadap Atribut-Atribut Kualitas Audit: Studi Perception Gap - Ari Budi Kristanto (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2012)
This research is conducted to test whether there are perception gaps existing between client and auditor about the importance of each audit quality attributes, that influence toward the client satisfaction. The form of the gaps can be used as the inputs for audit firm’s service improvement, on its relation to the client satisfaction. The samples of this research are taken from the companies located in Central Java which use audit service provided by audit firm, and auditors working at the audit firms in Central Java. Two means paired test are used for testing the gaps existence. Based on the research, among 6 tested attributes, there are gaps on 2 attributes, they are the strong commitment on audit quality, and audit firm’s leader’s involvement.Keywords : audit quality attributes, perception gap.